Does an Eczema Action Plan Improve Atopic Dermatitis? A Single-Site Randomized Controlled Trial. (December 2018) - Brown, Julia; Weitz, Nicole W.; Liang, Amy; Stockwell, Melissa S.; Friedman, Suzanne
The multitude of treatment options for atopic dermatitis (AD) makes management frustrating for providers and patients. Eczema action plans (EAPs) have been proposed to improve parental and provider management. We developed a single-site randomized controlled trial to evaluate the impact of an EAP on quality of life (QOL), provider knowledge, and comfort with AD management. Providers were randomized into an EAP-use group and a traditional care group. All patients completed validated AD QOL surveys, and those with AD were verbally administered the survey 1 month later. Providers' perceptions on managing AD were compared in the EAP and usual use groups. Parents in the EAP group demonstrated a significantly increased understanding of AD treatment, and providers in the EAP group had a significantly increased understanding and management of AD. The EAP is a feasible tool that can be integrated into a busy clinic practice with a positive impact on physicians and patients.